El tiempo en la historia y la emancipación en la filosofía de Guy Debord: Time in History and Emancipation in the Philosophy of Guy Debord - de Rivera, Javier (Universidad del Zulia, 2021)
Time plays a central role in Guy Debord's theory. In the society of the spectacle (1967) he dedicates two chapters to it, first in reference to the relationship of time and history, and later to explain its role in the creation of the spectacle. In both cases he resorts to different ways of living in time to explain different social and historical modalities. Behind his cryptic and concentrated style there are deep reflections regarding the meaning of the different times around which society is built, each of which produces different effects and realities. And even more, he uses time as a central reference to understand the processes of alienation and domination, as well as its counterpart, the proposal for the liberation of society that he proposes to us in his work. On the other hand, Debord builds on multiple theoretical influences that are articulated and intermingled in his text organically, and that are not always easily identifiable, largely due to the practice of deviation. We will begin by addressing the different modes of time, to see the function they have in history, as well as their role in the processes of social and spectacular alienation. From there we will expose the liberation proposal that he raises, and we will end with a brief recovery of the theoretical influences that mark his perspective on time and society.